Guaranteed Minimum Income – Form of Social Assistance for Poor Families in Romania - Mihăilescu, Adina (Calitatea Vieții, 2014)
Guaranteed minimum income (GMI) is a form of social assistance and ensures by providing monthly financial assistance. GMI has been the subject of profound reformation by eliminating errors over inclusion and efficient expenditure by rechecking eligibility allocation by beneficiary participation in the labor market and various community works. Amid objective efficient social spending and increased transparency in 2010 was the proposed elimination of GMI, along with other family benefits and the concept of minimum income of insertion, which was to strengthen and simplify helping low-income families. Minimum income of insertion proposed in 2011 is being implemented this year, 2014. In this article we analyze the dynamics of consumption and income of the families with children in high risk of poverty or even in chronic poverty, receiving minimum income compared to decent subsistence and the subsistence minimum calculated at the Research Institute for Quality of Life normative method, on types of families and area of residence.